Intrahepatic Viral Kinetics During Direct-Acting Antivirals for Hepatitis C in Human Immunodeficiency Virus Coinfection: The AIDS Clinical Trials Group A5335S Substudy. (23rd March 2020) - Balagopal, Ashwin; Smeaton, Laura M; Quinn, Jeffrey; Venuto, Charles S; Morse, Gene D; Vu, Vincent; Alston-Smith, Beverly; Cohen, Daniel E; Santana-Bagur, Jorge L; Anthony, Donald D; Sulkowski, Mark S; Wyles, David L; et al.
Abstract: Background: Direct-acting antivirals (DAAs) targeting hepatitis C virus (HCV) have revolutionized outcomes in human immunodeficiency virus (HIV) coinfection. Methods: We examined early events in liver and plasma through A5335S, a substudy of trial A5329 (paritaprevir/ritonavir, ombitasvir, dasabuvir, with ribavirin) that enrolled chronic genotype 1a HCV-infected persons coinfected with suppressed HIV: 5 of 6 treatment-naive enrollees completed A5335S. Results: Mean baseline plasma HCV ribonucleic acid (RNA) = 6.7 log10 IU/mL and changed by −4.1 log10 IU/mL by Day 7. In liver, laser capture microdissection was used to quantify HCV. At liver biopsy 1, mean %HCV-infected cells = 25.2% (95% confidence interval [CI], 7.4%–42.9%), correlating with plasma HCV RNA (Spearman rank correlation r = 0.9); at biopsy 2 (Day 7 in 4 of 5 participants), mean %HCV-infected cells = 1.0% (95% CI, 0.2%–1.7%) ( P  < .05 for change), and DAAs were detectable in liver. Plasma C-X-C motif chemokine 10 (CXCL10) concentrations changed by mean = −160 pg/mL per day at 24 hours, but no further after Day 4. Conclusions: We conclude that HCV infection is rapidly cleared from liver with DAA leaving <2% HCV-infected hepatocytes at Day 7. We extrapolate that HCV eradication could occur in these participants by 63 days, although immune activation might persist. Single-cell longitudinal estimates of HCV clearance from liver have never been reported previously and could be applied to estimating the minimum treatment duration required for HCV infection. Abstract : Intrahepatic study of hepatitis C treatment in HIV coinfection reveals rapid removal of HCV RNA but slower resolution of immune activation.